Investigation and management of hypocalcaemia. Issue 4 (3rd January 2020) - Nadar, Ruchi; Shaw, Nick
Abstract : Hypocalcaemia is a common clinical scenario in children with a range of aetiological causes. It will often present with common symptoms but may occasionally be identified in an asymptomatic child. An understanding of the physiological regulation of plasma calcium is important in understanding the potential cause of hypocalcaemia and its appropriate management. The age of presentation will influence the likely differential diagnosis. We have presented a stepwise approach to the investigation of hypocalcaemia dependent on the circulating serum parathyroid hormone level at the time of presentation. The acute and long-term management of the underlying condition is also reviewed.